2019
DOI: 10.3390/cells8060627
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Involvement in Melanoma. Potentials for Detection of Disseminated Tumor Cells and Characterization of Their Subsets by Flow Cytometry

Abstract: Disseminated tumor cells (DTCs) are studied as a prognostic factor in many non-hematopoietic tumors. Melanoma is one of the most aggressive tumors. Forty percent of melanoma patients develop distant metastases at five or more years after curative surgery, and frequent manifestations of melanoma without an identified primary lesion may reflect the tendency of melanoma cells to spread from indolent sites such as bone marrow (BM). The purpose of this work was to evaluate the possibility of detecting melanoma DTCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 26 publications
0
9
0
13
Order By: Relevance
“…The study of hematopoiesis in patients with breast cancer revealed a number of patterns that we had noted in earlier studies with squamous cell carcinoma of the head and neck, melanoma, and also with lymphomas [12,13]. A decrease in the populations of basophilic and polychromatophilicnormoblasts and an increase in oxyphilic forms have been established.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The study of hematopoiesis in patients with breast cancer revealed a number of patterns that we had noted in earlier studies with squamous cell carcinoma of the head and neck, melanoma, and also with lymphomas [12,13]. A decrease in the populations of basophilic and polychromatophilicnormoblasts and an increase in oxyphilic forms have been established.…”
Section: Discussionmentioning
confidence: 58%
“…A decrease in the populations of basophilic and polychromatophilicnormoblasts and an increase in oxyphilic forms have been established. It is important to note that such observations often occurred in cases of bone marrow involvement in the tumor process, for example, with melanoma [13]. In this study, we did not provide data on the presence of breast cancer micrometastases in the bone marrow; there was no lesion in all cases at the morphological level.…”
Section: Discussionmentioning
confidence: 70%
“…В настоящее время усилия ученых направлены на разработку различных стратегий повышения эффективности противоопухолевого иммунного ответа, и значительная доля научных исследований посвящена изучению иммунобиологических механизмов гематогенного метастазирования [2][3][4]. Предметом пристального внимания в этом контексте стали диссеминированные опухолевые клетки (ДОК), которые довольно часто обнаруживаются в костном мозге (КМ) онкологического больного [5][6][7][8]. Следует подчеркнуть, что практически у 40 % таких больных имеются ранние стадии опухолевого процесса.…”
Section: Introductionunclassified
“…Эти процессы приводят к приобретению ими новых фенотипических признаков. В недавней работе показана гетерогенность ДОК: они экспрессируют на своей поверхности разнообразный набор антигенов [7], что отличает их от первичной опухоли и отражает сложную архитектуру отношений между ДОК и микроокружением. Имеются данные, что ДОК в КМ могут иметь геномные профили, не связанные с первичной опухолью [13].…”
Section: Introductionunclassified
“…Chernysheva et al studied disseminated tumor cells (DTCs) as a prognostic factor in many non-hematopoietic tumors [9]. They evaluated the possibility of detecting subsets of melanoma DTCs in the bone marrow based on the expression of a cytoplasmic premelanocytic glycoprotein HMB-45 using flow cytometry.…”
mentioning
confidence: 99%